Applications of NMR spectroscopy in understanding the gold biochemistry. Issue 3 (2006) - Isab Isab, Anvarhusein A. Anvarhusein A.; Ahmad Ahmad, Saeed Saeed
Abstract : Gold-based drugs have been successfully used for the treatment of rheumatoid arthritis. When administered, they undergo ligand exchange reactions in the body with biofluids, cells and proteins. NMR spectroscopy is a very useful technique for probing these ligand exchange reactions under physiological conditions. The strength of the binding ligands can be estimated by studying the chemical shift changes in 13 C and 31 P NMR. It is also a powerful method for investigating the kinetics and thermodynamics of the exchange reactions of gold drugs with biomolecules. The purpose of this review report is to highlight the importance of NMR spectroscopy in the study of gold biochemistry and to bridge the fairly large gap in the progress of this interesting area of bioinorganic chemistry.